Escherichia coli Mutants Thermosensitive for Deoxyribonucleic Acid Gyrase Subunit A: Effects on Deoxyribonucleic Acid Replication, Transcription, and Bacteriophage Growth - Kreuzer, Kenneth N. (1979)
Temperature-sensitive nalA mutants of Escherichia coli have been used to investigate the structure and functions of deoxyribonucleic acid (DNA) gyrase. Extracts of one such mutant (nalA43) had thermosensitive DNA gyrase subunit A activity but normal gyrase subunit B activity, proving definitively that nalA is the structural gene for subunit A. Extracts of a second nalA (Ts) mutant (nalA45) had a 50-fold deficiency of gyrase subunit A activity. The residual DNA supertwisting was catalyzed by the mutant DNA gyrase rather than by a novel supertwisting enzyme. The nalA45(Ts) extract was also deficient in the nalidixic acid target, which is defined as the protein necessary to confer drug sensitivity to in vitro DNA replication directed by a nalidixic acid-resistant mutant extract. Thus, gyrase subunit A and the nalidixic acid target are one and the same protein, the nalA gene product. Shift of the nalA43(Ts) mutant to a nonpermissive temperature resulted in a precipitous decline in the rate of [(3)H]thymidine incorporation, demonstrating an obligatory role of the nalA gene product in DNA replication. The rates of incorporation of [(3)H]uridine pulses and continuously administered [(3)H]uracil were quickly reduced approximately twofold upon temperature shift of the nalA43(Ts) mutant, and therefore some but not all transcription requires the nalA gene product. The thermosensitive growth of bacteriophages φX174 and T4 in the nalA43(Ts) host shows that these phages depend on the host nalA gene product. In contrast, the growth of phage T7 was strongly inhibited by nalidixic acid but essentially unaffected by the nalA43(Ts) mutation. The inhibition of T7 growth by nalidixic acid was, however, eliminated by temperature inactivation of the nal43 gene product. Therefore, nalidixic acid may block T7 growth by a corruption rather than a simple elimination of the nalidixic acid target. Possible mechanisms for such a corruption are considered, and their relevance to the puzzling dominance of drug sensitivity is discussed.